The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2105/ajph.2017.303769
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2016 Ecuador Earthquake on Zika Virus Cases

Abstract: Objectives. To evaluate the impact of the April 2016 7.8-magnitude earthquake in Ecuador on the incidence of Zika virus (ZIKV) cases.Methods. We used the national public health surveillance system for reportable transmissible conditions and included suspected and laboratory-confirmed ZIKV cases. We compared the number of cases before and after the earthquake in areas closer to and farther from the epicenter.Results. From January to July 2016, 2234 patients suspected of having ZIKV infection were reported in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…Our preliminary research had already suggested an increase in post-earthquake incident ZIKV cases in Ecuador during the period January-July 2016 44 . A later study confirmed this observation 45 . However, neither of these studies controlled for socioeconomic and climatic variables nor did they evaluate the impact of climatic context on this phenomenon, which might confound the observed associations.…”
Section: Discussionmentioning
confidence: 52%
“…Our preliminary research had already suggested an increase in post-earthquake incident ZIKV cases in Ecuador during the period January-July 2016 44 . A later study confirmed this observation 45 . However, neither of these studies controlled for socioeconomic and climatic variables nor did they evaluate the impact of climatic context on this phenomenon, which might confound the observed associations.…”
Section: Discussionmentioning
confidence: 52%
“…(4) Las ETV aumentaron a raíz de los desastres naturales en regiones de Sudamérica y Centroamérica. (5) . Ningún otro continente notificó brotes de ZIKV en magnitud similar a lo observado en Sudamérica, donde los cambios meteorológicos de "El Niño" fueron considerados los desencadenantes iniciales de la epidemia en Brasil.…”
Section: Introductionunclassified
“…Ningún otro continente notificó brotes de ZIKV en magnitud similar a lo observado en Sudamérica, donde los cambios meteorológicos de "El Niño" fueron considerados los desencadenantes iniciales de la epidemia en Brasil. (5) La mayor transmisión de ZIKV a nivel mundial se produjo a inicios del año 2016, posterior a lo cual disminuyó considerablemente. (6,7) Sin embargo, el calentamiento global y las características poblacionales de pobreza produjeron una segunda oleada de transmisión de ZIKV en Ecuador, Perú y Argentina durante el primer semestre del año 2017.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…There were 660 reported fatalities, 4605 people with injuries, 30,223 people displaced, 9738 buildings damaged/destroyed and roughly 720,000 people requiring humanitarian assistance [ 1 ]. The earthquake triggered a major epidemic of Zika virus (ZIKV) [ 2 ], a major health concern due to the complications associated with infection, such as Guillain-Barre Syndrome and congenital syndrome [ 3 ]. Following the earthquake, the cumulative number of ZIKV cases in Ecuador increased from 103 cases in epidemiological week 14 of 2016 to 1275 cases in epidemiological week 25 of 2016, with 85% of all ZIKV cases in 2016 reported from Manabí Province, near the epicenter ( Figure 1 and Figure 2 ) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%